Transposisi Catford dalam Penerjemahan Jepang-Indonesia Novel Kaki no Ki no Aru Ie Karya Tsuboi Sakae - Vancelin, Nathania Mariany; Andarwati, Titien Wahyu; Suryawati, Cicilia Tantri (KIRYOKU, 2026)
This applied linguistics study aims to describe translation shifts based on Catford’s (1978) theory, including level shifts and category shifts (structure shifts, class shifts, unit shifts, and intra-system shifts), as one of the translation strategies found in the classic Japanese novel Kaki no Ki no Aru Ie and its Indonesian translation Rumah Pohon Kesemek. This research offers novelty, as studies on transposition from Japanese into Indonesian novels remain limited. Using a descriptive qualitative approach, the data consist of narrative texts drawn from the two versions of the novel as primary sources. The data were analyzed through a translational equivalence method combined with syntactic functional and categorical analysis to identify the types of shifts employed. Results show that among 278 data items, level shifts and all types of category shifts occur in the novel, with some cases classified into more than one shift type. Level shifts involve changes from grammar to lexis and from lexis to grammar, often realized through affixation. Among the four category shifts, structure shifts are the most frequent due to differences in standard sentence patterns between the SL and TL (SOV–SVO and MH-HM). It is concluded that transposition plays an important role in Japanese–Indonesian translation, and translators need strong understanding of both grammatical systems to produce natural and acceptable translations for Indonesian readers. These findings may serve as a reference for future studies with more specific data selection criteria, such as complex sentences in the SL rendered as multiple sentences in the TL.